Antonio Méndez Rubio, (FBI). Fascismo de baja intensidad (Altre Modernità, 2016)
Antonio Méndez Rubio, (FBI). Fascismo de baja intensidad(Santander, LaVorágine, 2015, 95 pp. s/ISBN)di Gabriele Gelmini